2017
DOI: 10.1007/s10753-017-0654-x
|View full text |Cite
|
Sign up to set email alerts
|

Gypenoside IX Suppresses p38 MAPK/Akt/NFκB Signaling Pathway Activation and Inflammatory Responses in Astrocytes Stimulated by Proinflammatory Mediators

Abstract: Gypenoside IX (GP IX) is a pure compound isolated from Panax notoginseng. Gypenosides have been implicated to benefit the recovery of enormous neurological disorders. By suppressing the activation of astrocytes, gypenosides can improve the cognitive impairment. However, so far, little is known about whether GP IX could restrain the inflammatory responses in astrocytes or reactive astrogliosis. In present study, the anti-inflammatory effects of GP IX were investigated in reactive astrocytes induced by proinflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…During pathological conditions involving CNS inflammation, IL-1β is mainly released by activated macrophages and microglia, and astrocytes are regarded as the major target of IL-1β, as suggested by the presence of IL-1β receptors on the surfaces of astrocytes [ 27 ]. In astrocytes, IL-1β induces the expression of other cytokines, including IL-6 and TNF-α, as well as other inflammatory mediators that have been implicated in the CNS immune response to injury [ 28 ]. Interestingly, systemic LPS and IL-1β injections have been reported to induce excess COX-2 production within the rodent brain [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…During pathological conditions involving CNS inflammation, IL-1β is mainly released by activated macrophages and microglia, and astrocytes are regarded as the major target of IL-1β, as suggested by the presence of IL-1β receptors on the surfaces of astrocytes [ 27 ]. In astrocytes, IL-1β induces the expression of other cytokines, including IL-6 and TNF-α, as well as other inflammatory mediators that have been implicated in the CNS immune response to injury [ 28 ]. Interestingly, systemic LPS and IL-1β injections have been reported to induce excess COX-2 production within the rodent brain [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several hours later (6, 12, 24, 36 and 48 hours), the supernatant of H9C2 cells was obtained to detect cell vitality using LDH. MTS, TUNEL and FCM were used to analyse cell vitality and cell apoptosis, which have been described in previous publications …”
Section: Methodsmentioning
confidence: 99%
“…As a traditional Chinese medicine, Gynostemma pentaphylla ( Thunb .) Makino exerts anti‐hypertensive, anti‐ageing, anti‐hyperlipidemia, anti‐hyperglycaemia and anti‐inflammation effects . As a result, Gynostemma has been used to improve symptoms of several diseases for centuries, including hyperlipidemia, hepatitis, atherosis and diabetes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gyp has various biological activities, including roles in anti-inflammatory reactions, insulin resistance, reducing memory deficits, and decreasing liver fibrosis [11,12]. Moreover, Gyp IX inhibits NFκB transcriptional activity and reduced the expression of several inflammatory factors, including nitric oxide synthase (iNOS), tumour necrosis factor-α (TNF-α), and interleukin-1β (IL-1β) [11]. Qin and colleagues showed that Gyp influences lipid metabolism, reduces oxidative stress, inhibits mitochondrial damage, and prevents degeneration in fatty liver disease [13].…”
Section: Introductionmentioning
confidence: 99%